Striatal But Not Extrastriatal Dopamine Receptors Are Critical to Dopaminergic Motor Stimulation - Wang, Yuhan; Zhou, Fu-Ming (Frontiers in Pharmacology, 2017)
Dopamine (DA) is required for motor function in vertebrate animals including humans. The striatum, a key motor control center, receives a dense DA innervation and express high levels of DA D1 receptors (D1Rs) and D2 receptors (D2Rs). Other brain areas involved in motor function such as the globus pallidus external segment (GPe) and the substantia nigra pars reticulata (SNr) and the motor cortex also receive DA innervation and express DA receptors. Thus, the relative contribution of the striatal and extrastriatal DA systems to the motor function has been an important question critical for understanding the functional operation of the motor control circuits and also for therapeutic targeting. We have now experimentally addressed this question in the transcription factor Pitx3 null mutant mice that have an autogenic and parkinsonian-like striatal DA denervation and hence supersensitive motor response to DA stimulation. Using DA agonist unilateral microinjection-induced rotation as a reliable readout of motor stimulation, our results show that L-dopa microinjection into the dorsal striatum induced 5-10 times more rotations than that induced by L-dopa microinjection into GPe and SNr, while L-dopa microinjection into the primary motor cortex induced the least number of rotation. Furthermore, our results show that separate microinjection of the D1R-like agonist SKF81297 and the D2R-like agonist ropinirole into the dorsal striatum (DS) each induced only modest numbers of rotation, whereas concurrent injection of the two agonists triggered more rotations than the sum of the rotations induced by each of these two agonists separately, indicating D1R-D2R synergy. These results suggest that the striatum, not GPe, SNr or motor cortex, is the primary site for D1Rs and D2Rs to synergistically stimulate motor function in L-dopa treatment of Parkinson's disease (PD). Our results also predict that non-selective, broad spectrum DA agonists activating both D1Rs and D2Rs are more efficacious anti-PD drugs than the current D2R agonists.